Nonverbal sensitivity, verbal communication, and team coordination in tennis doubles - Lausic, D.; Razon, S.; Tenenbaum, GT (International Journal of Sport and Exercise Psychology, 2015)
To advance the extant literature on message exchange framework, the current study represents an initial attempt to evaluate verbal communication in sport teams as it relates to (a) nonverbal communication sensitivity and (b) competitive performance. Verbal communication behaviours in a National Collegiate Athletic Association Division I male tennis team were observed during doubles matches. These were subsequently related to the players' nonverbal sensitivity scores measured by the Profile of Nonverbal Sensitivity (PONS) test. To capture between-the-point communication, matches were videotaped. Verbal communication data were coded and analysed using the Data Analysis Tool software. The results indicated that relative to their losing counterparts, winning players exhibited greater levels of verbal communication and had a tendency to score higher on the nonverbal sensitivity items in the PONS. Specifically, relative to losing teams who made greater use of nontask-related statements, winning teams made frequent use of emotional, action, encouragement, and planning statements. Communication patterns within the winning teams were also more homogenous and reliable. Moreover, the players in these teams were more sensitive to nonverbal cues, which potentially enhanced communication and game planning for these teams.